2021
DOI: 10.1101/2021.01.28.21250466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Seroepidemiology in Children and Adolescents

Abstract: ObjectivesPediatric SARS-CoV-2 data remain limited and seropositivity rates in children were reported as <1% early in the pandemic. Seroepidemiologic evaluation of SARS-CoV-2 in children in a major metropolitan region of the United States was performed.MethodsChildren and adolescents ≤19 years were enrolled in a cross-sectional, observational study of SARS-CoV-2 seroprevalence from July-October 2020 in Northern Virginia, United States. Demographic, health, and COVID-19 exposure information was collected, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…41 Our findings are in accordance with other seroprevalence studies, where socioeconomic contexts are found to play a lead role in terms of SARS-CoV-2 exposure risk and infection. Higher exposure rates have been found in ethnic minority populations, 30,42 children living in poverty, inadequate dwelling conditions, 42 among others. These contextual factors should be accounted for when planning public health interventions aimed to mitigate SARS-CoV-2 impacts.…”
Section: Discussionmentioning
confidence: 99%
“…41 Our findings are in accordance with other seroprevalence studies, where socioeconomic contexts are found to play a lead role in terms of SARS-CoV-2 exposure risk and infection. Higher exposure rates have been found in ethnic minority populations, 30,42 children living in poverty, inadequate dwelling conditions, 42 among others. These contextual factors should be accounted for when planning public health interventions aimed to mitigate SARS-CoV-2 impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors. The most densely populated centres were the most affected by COVID-19 [8,16,20,32,40,41,48,50,53,55,56,59,71,76,78,81,86,87,88,91,92,94,95,101,102,106,[115][116][117][118][119][120][121][122][123][124][125][126]. Sex was examined in 14 studies, which found mostly no significant difference (one a higher seroprevalence in men and 6 a higher seroprevalence in women).…”
Section: Plos Onementioning
confidence: 99%
“…The seroprevalence was two times higher with low than high education [91]. Thirteen studies showed that the risk of seropositivity increased by about 30% with a confirmed COVID-19 case in the household [23,32,36,47,55,59,68,75,79,88,92,125,136]. Ten studies showed that the risk of seropositivity increased with the number of children in the household [16,25,55,71,77,88,116,120,125,133].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation